ANALYSIS ON ONLINE DISTANCE LEARNING OF MECHANICAL ENGINEERING LABORATORY COURSE FOR ACADEMIC SUSTAINABILITY IN TERTIARY EDUCATION - Norliana Mohd Abbas; Muhammad Hakimi Abdul Wahab; Noriah Yusoff (Journal of Islamic, Social, Economics and Development, 2024)
In previous years, laboratory courses are usually being conducted physically. This is because, the course requires hands-on learning such as access to specialized equipment, material, and experience. As the computer technologies evolves and the expansion of internet reachability, virtual laboratory was steadily developed for better accessibility, flexibility, safety and cost-effective. However, the global pandemic of COVID-19 has forces sudden implementation of laboratory online learning and created a new norm in the teaching and learning. This study aims to investigate the suitability of online learning of Mechanical Engineering laboratory course in the future. The investigation was done by disseminating a set of questionnaires to the target respondents. The validity and reliability of the survey questions were confirmed through a pilot test of 50 respondents by using Principal Component Analysis (PCA) and Cronbach Alpha (CA). The responses in five-Likert scale results were then further classified into three categories: Good, Non-decisive and Poor. The findings were compared against students’ grades to validate the performance. The survey results indicated that the students gained good learning engagement (51%) and experience (46%), respectively. The suitability (64%), delivery (60%) and communication (44%) satisfy the ‘Good’ category hence affirmed the students’ good online learning experience. The student’s grades of the course exhibits correlation with the survey response. All the student passed the course with 8% A’s, 34% B’s and 58% C’s.